Sengketa Ekonomi Syariâah (Antara Kompetensi Pengadilan Agama dan Badan Arbitrase Syariâah) - Timorita Yulianti, Rahmani (Al-Mawarid Jurnal Hukum Islam, 2007)
The legislating Act No. 3 year 2006 regarding the amending Act No.7year 1979 concerning Islamic Court in Indonesia has implied the fundamental changing toward the existence of Islamic court nowadays. One of the changing is adding or enlarging of Islamic court jurisdiction for handling Syariâah economics. According to article 49 (i) of Act No.3 year 2006 declares that Islamic court has jurisdiction to handle the cases of Syariâah economics. This implies that The judges of Islamic courtshould master Syariâah economics knowledge.TBut this also influences on the existence of National Syariâah Abritase council (Badan Abritase Syariah Nasional) in term of Syariâah economics cases handling. Kata kunci: Sengketa, kompetensi, arbitrase Syariâah, dan peradilan agama.